Theoretical global seismology - Dahlen, F. A., 1942-; Tromp, Jeroen (Princeton, N.J. : Princeton University Press, 1998)
After every major earthquake, the Earth rings like a bell for several days. These free oscillations of the Earth and the related propagating body and surface waves are routinely detected at broad-band seismographic stations around the world. In this comprehensive treatise, Dahlen and Tromp present an up-to-date and advanced theoretical treatment of global seismology, describing the normal-mode-body-wave, and surface-wave methods employed in the determination of the Earth's three-dimensional internal structure and the source mechanisms of earthquakes. As a long-needed unification of methods and results in this active research area.
Theoretical Global Seismology will be important to graduate students in geophysics and allied fields, as well as to seismologists, geodynamicists, geomagnetists, and astronomers who study the oscillations of the Sun and other stars.
Ch. 1. Historical Introduction -- Ch. 2. Continuum Mechanics -- Ch. 3. Equations of Motion -- Ch. 4. Normal Modes -- Ch. 5. Seismic Source Representation -- Ch. 6. Anelasticity and Attenuation -- Ch. 7. Rayleigh-Ritz Method -- Ch. 8. Spheroidal and Toroidal Oscillations -- Ch. 9. Elastic and Anelastic Perturbations -- Ch. 10. Synthetic Seismograms -- Ch. 11. Love and Rayleigh Waves -- Ch. 12. Mode-Ray Duality -- Ch. 13. Perturbation Theory -- Ch. 14. Mode Splitting and Coupling -- Ch. 15. Body-Wave Ray Theory -- Ch. 16. Surface-Wave JWKB Theory -- App. A. Vectors and Tensors -- App. B. Spherical Harmonics -- App. C. Generalized Spherical Harmonics -- App. D. Whole Earth Catalogue.
Includes bibliographical references (pages 967-997) and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Seismology; Sismologie; SCIENCE -- Earth Sciences -- General; Seismology; Seismologie; SEISMOLOGY; CONTINUUM MECHANICS; MOTION; Sismologie